Moderating role of foreign investor characteristics over the relationship between regulatory and economic dimensions of foreign direct investment and environmental degradation in UAE - Albahar, Saood Mohammad Hassan (2024)
Dubai is among the fastest-growing economies in the Arab world and is attracting foreign direct investment at its best. However, at the same time, environmental issues are also a major concern for the UAE. Therefore, the purpose of the study is to identify the moderating role of foreign investor characteristics in the relationship between regulatory and economic dimensions of FDI and environmental degradation in the UAE. In order to meet the objectives of the study, four hypotheses were developed. The first and second hypotheses deal with the direct effect of regulatory and economic dimensions of foreign direct investment, whereas the third and fourth hypotheses deal with the moderating impact of foreign investor characteristics on the relationship between regulatory and economic dimensions of FDI and environmental degradation. With the underpinning support of internationalization theory, all the hypotheses have been checked through the primary data. The data was collected from the executives of multinational companies operating in Dubai. The findings of the study revealed that the regulatory and economic dimensions of FDI have a significant impact on environmental degradation. Likewise, foreign investor characteristics play a significant moderating role in the significant relationship between the regulatory and economic dimensions of FDI and environmental degradation. The research contributes significantly to the internationalization theory by identifying the moderating role of foreign investor characteristics, which was a missing element in the theory. However, the study has also shown some limitations and opened the horizons for future research.